2014
DOI: 10.1055/s-0033-1363771
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pentoxifylline and/or IgM-Enriched Intravenous Immunoglobulin in the Management of Neonatal Sepsis

Abstract: PTX and IgM-enriched IVIG therapies, either alone or in combination, did not reduce the rates of morbidities and mortality in NS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 19 publications
2
64
0
Order By: Relevance
“…TNF-α and platelet activating factor are the most important among proinflammatory cytokines that have been implicated in the development of NEC. Recently, Akdag et al 21 have shown that 2 patients in the PTX group developed NEC compared with 2 patients in the placebo group, and statistical analysis was not applicable because of the small number of cases. In contrast, Erdener et al 36 have demonstrated that intraperitoneal PTX pretreatment in newborn rabbits did not have a protective effect on NEC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…TNF-α and platelet activating factor are the most important among proinflammatory cytokines that have been implicated in the development of NEC. Recently, Akdag et al 21 have shown that 2 patients in the PTX group developed NEC compared with 2 patients in the placebo group, and statistical analysis was not applicable because of the small number of cases. In contrast, Erdener et al 36 have demonstrated that intraperitoneal PTX pretreatment in newborn rabbits did not have a protective effect on NEC.…”
Section: Discussionmentioning
confidence: 99%
“…19,21,26 The following laboratory investigations were done in all infants with suspicion of LOS: total and differential leukocyte count and assessment of serum C-reactive protein (CRP). 19,21,26 The following laboratory investigations were done in all infants with suspicion of LOS: total and differential leukocyte count and assessment of serum C-reactive protein (CRP).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Granulocyte-CSF (G-CSF) and granulocyte-macrophage CSF (GM-CSF) cannot be recommended in neonatal sepsis. (b) IgGs are effective in adults with sepsis [45] but not in low-birth weight newborns (<1,500 g) [46] or in newborns with gestational ages of 31 to 42 weeks [47]. (c) A meta-analysis on the efficacy of immuno-modulating diets reported that they had no effect on mortality or length of stay of critically ill patients [48].…”
Section: Managementmentioning
confidence: 99%